Active immunization with human interleukin-15 induces neutralizing antibodies in non-human primates. (December 2016) - Rodríguez-Álvarez, Yunier; Morera-Díaz, Yanelys; Gerónimo-Pérez, Haydee; Castro-Velazco, Jorge; Martínez-Castillo, Rafael; Puente-Pérez, Pedro; Besada-Pérez, Vladimir; Hardy-Rando, Eugenio; Chico-Capote, Araceli; Martínez-Cordovez, Klaudia; Santos-Savio, Alicia
Abstract Background Interleukin-15 is an immunostimulatory cytokine overexpressed in several autoimmune and inflammatory diseases such as Rheumatoid Arthritis, psoriasis and ulcerative colitis; thus, inhibition of IL-15-induced signaling could be clinically beneficial in these disorders. Our approach to neutralize IL-15 consisted in active immunization with structurally modified human IL-15 (mhIL-15) with the aim to induce neutralizing antibodies against native IL-15. In the present study, we characterized the antibody response inMacaca fascicularis, non-human primates that were immunized with a vaccine candidate containing mhIL-15 in Aluminum hydroxide (Alum), Montanide and Incomplete Freund's Adjuvant. Results Immunization with mhIL-15 elicited a specific antibodies response that neutralized native IL-15-dependent biologic activity in a CTLL-2 cell proliferation assay. The highest neutralizing response was obtained in macaques immunized with mhIL-15 adjuvanted in Alum. This response, which was shown to be transient, also inhibited the activity of simian IL-15 and did not affect the human IL-2-induced proliferation of CTLL-2 cells. Also, in a pool of synovial fluid cells from two Rheumatoid Arthritis patients, the immune sera slightly inhibited TNF-α secretion. Finally, it was observed that this vaccine candidate neither affect animal behavior, clinical status, blood biochemistry nor the percentage of IL-15-dependent cell populations, specifically CD56+ NK and CD8+ T cells. Conclusion Our results indicate that vaccination with mhIL-15 induced neutralizing antibodies to native IL-15 in non-human primates. Based on this fact, we propose that this vaccine candidate could be potentially beneficial for treatment of diseases where IL-15 overexpression is associated with their pathogenesis.